2020
DOI: 10.3846/aviation.2020.13290
|View full text |Cite
|
Sign up to set email alerts
|

Airport Service Quality: A Reconceptualization and a Practical Application on the Non-Aeronautical Services

Abstract: In line with the advancing airway capability, the non-aeronautical business opportunities at airports are also in growth. To attract more passengers or to generate extra income over non-aeronautical services, the airport decision-makers need to evaluate the quality of their services. This study aims at introducing an expanded approach to improve airport service quality aspects of the non-aeronautical business opportunities. Given the increasing number of airports, passengers prefer airports, which provide bett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…In airport literature, the term "service quality" refers to superiority or excellence in service delivery [20,21]. In other words, service quality reflects the gap between customers' expectations and the perception of the service received [22].…”
Section: Literature Review and Hypotheses Formulation 21 Airport Serv...mentioning
confidence: 99%
See 1 more Smart Citation
“…In airport literature, the term "service quality" refers to superiority or excellence in service delivery [20,21]. In other words, service quality reflects the gap between customers' expectations and the perception of the service received [22].…”
Section: Literature Review and Hypotheses Formulation 21 Airport Serv...mentioning
confidence: 99%
“…Along with defining sufficient and necessary antecedents for passenger satisfaction, this study utilizes online reviews in airport research, an area that remains under-researched [15]. Thus, while the current literature analyzes online reviews in the air transport sector using a variety of methods, including multinominal logistic regression [7], one-way ANOVA [69], sentiment analysis [67], response surface analysis [93], latent semantic analysis [39], PLS path modeling [40], content analysis [20], structural topic modeling [94], and CONCOR analysis [37], this study applied the NCA method for the first time. Finally, this study is one of the few that examines passenger satisfaction in the post-COVID-19 era [95][96][97][98].…”
Section: Complementary Analysis For Post-covid-19 Periodmentioning
confidence: 99%
“…Moreover, Bulut and Aydogan (2020) [39] revealed that the decision-makers should improve the passenger service quality. It helps decision-makers where to focus as a strategic priority.…”
Section: Airport Service Quality As a Distinctive To Empower The Bran...mentioning
confidence: 99%